TOTALLY UMBILICAL CR-SUBMANIFOLDS OF A KAEHLER MANIFOLD - HAIDER, S. M. KHURSHEED; KHAN, V. A.; HUSAIN, S . I. (Tamkang Journal of Mathematics, 1993)
In the present paper we study totally umbilical CR-submanifolds of a Kaehler manifold. A classification theorem for a $D^\perp$-totally umbilical CR-submanifold is proved. The conditions under which a CR- submanifold becomes a CR-product are obtained, and finally a theorem for a CR-submanifold to be a proper CR-product is also established.